Relationships between Electrokinetic Index of buccal epithelium and some functional and metabolic parameters at men with chronic pyelonephrite - Kyrylenko, Iryna G.; Fajda, Oleksandra I.; Drach, Oleksandr V.; Popel’, Svitlana L.; Popel’, Roman L.; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Kyrylenko Iryna G., Fajda Oleksandra I., Drach Oleksandr V., Popel’ Svitlana L., Popel’ Roman L., Zukow Walery. Relationships between Electrokinetic Index of buccal epithelium and some functional and metabolic parameters at men with chronic pyelonephrite. Journal of Education, Health and Sport. 2016;6(1):302-314. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45361 http://ojs.ukw.edu.pl/index.php/johs/article/view/3369 https://pbn.nauka.gov.pl/works/710846 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. RELATIONSHIPS BETWEEN ELECTROKINETIC INDEX OF BUCCAL EPITHELIUM AND SOME FUNCTIONAL AND METABOLIC PARAMETERS AT MEN WITH CHRONIC PYELONEPHRITE Iryna G. Kyrylenko1,2, Oleksandra I. Fajda3, Oleksandr V. Drach4, Svitlana L. Popel’4, Roman L. Popel’4, Walery Zukow5 1Danylo Halyts’kyǐ National Medical University, L’viv, Ukraine pandka@ukr.net 2Laboratory of Experimental Balneology, OO Bohomolets’ Institute of Physiology NAS, Truskavets’-Kyiv, Ukraine i.popovych@ukr.net 3JSC „Dnipro-Beskyd“, Truskavets’, Ukraine alexavka7@gmail.com 4JSC “ Truskavets’kurort”, Truskavets’, Ukraine 5Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl Abstracts Background. Known for a number of parameters of the body, which through regression equations derived can assess biological age. We examined relationships between electrokinetic mobility buccal epithelium cell nuclei, named Electrokinetic Index (EKI), and some functional and metabolic parameters of body. Methods. Under a observations were 23 men by age 24-70 years with chronic pyelonephrite in the phase of remission. We estimated the EKI, state of the vegetative and hormonal regulation as well as metabolism of cholesterol. Results. We confirned closely correlation (r=-0,89) between Metric Age and EKI. Baevskiy’s Adaptation Potential and Stange’s Test together determines EKI on 28%. RMSSD, VLF and Baevskiy’s Stress Index determines EKI on 31%. Plasma Colesterol and Klimov’s Atherogenicity Coefficient determines EKI on 56%. In summary model of multiple regression with stepwise excluding are currently two last parameters as well as Plasma Testosterone and relative Power Spectral VLF HRV, which together determines EKI on 73%: R=0,868; R2=0,754; Adjusted R2=0,730;F(4,4)=31,4; χ2(4)=58,9; p<10-5. Conclusion. Electrokinetic Index of buccal epithelium really rellects neuro-endocrine regulation and metabolism of Cholesterol. Keywords: Electrokinetic Index, Biological Age, HRV, Cholesterol, Testosterone, Cortisol, Relationships.